2009
DOI: 10.1080/00207450902787165
|View full text |Cite
|
Sign up to set email alerts
|

Protection in Glutamate-Induced Neurotoxicity by Imidazoline Receptor Agonist Moxonidine

Abstract: In the present study we investigated the effects of mixed imidazoline-1 and alpha(2)-adrenoceptor agonist, moxonidine, in glutamate-induced neurotoxicity in frontal cortical cell cultures of rat pups by dye exclusion test. Also, phosphorylated p38 mitogen activated protein kinases (p-p38 MAPK) levels were determined from rat frontal cortical tissue homogenates by two dimensional gel electrophoresis and semidry western blotting. Glutamate at a concentration of 10(-6) M was found neurotoxic when applied for 16 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…1 and 2) in diabetic rats. These findings agree with neuroprotective effects of moxonidine against ischemic insults in neuronal cultures (Milhaud et al, 2000;Bakuridze et al, 2009) and against glutamate-evoked neurotoxicity (Keller and García-Sevilla, 2016). However, the mechanism of the neuroprotective effect of moxonidine was not investigated in the reported studies.…”
Section: H 2 S-dependent Neuroprotection By Moxonidine In Diabetessupporting
confidence: 76%
“…1 and 2) in diabetic rats. These findings agree with neuroprotective effects of moxonidine against ischemic insults in neuronal cultures (Milhaud et al, 2000;Bakuridze et al, 2009) and against glutamate-evoked neurotoxicity (Keller and García-Sevilla, 2016). However, the mechanism of the neuroprotective effect of moxonidine was not investigated in the reported studies.…”
Section: H 2 S-dependent Neuroprotection By Moxonidine In Diabetessupporting
confidence: 76%
“…L-glutamate is a standard neurotoxic stimulus that is a model of excitotoxic cell death (Choi et al 1987 ), and p38 has been reported to be involved in excitotoxic pathways leading to neuron damage/death (Kawasaki et al 1997 ; Chen et al 2003 ; Pi et al 2004 ; Chaparro-Huerta et al 2008 ; Molz et al 2008 ; Bakuridze et al 2009 ; Izumi et al 2009 ). Therefore, we compared the degree of neuron death and neurite degeneration induced by L-glutamate in primary cortical neurons derived from WT and p38β KO mice.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro experimental researches have shown that activation of I2 receptors via the agmatine endogenous ligand exerts neuroprotective effects by increasing the expression of glial fibrillary acidic protein in astrocyte cultures and by inhibiting MAO activity [26,27]. Moreover, the beneficial effects of agmatine have been observed on ischemic-hypoxic lesions, on glutamate-induced neurotoxicity by activating the imidazoline receptors [28,29].…”
Section: The Involvement Of the Imidazoline System In The Mediation Omentioning
confidence: 99%
“…In vitro cell culture studies from the rat frontal cortex with glutamate-induced neurotoxicity revealed the partial neuroprotective effects of moxonidine, with a significant decrease in the number of dead cells [26]. Moxonidine has shown beneficial effects on cerebral spasm in an experimental rabbit model of subarachnoid hemorrhage [40,56].…”
Section: The Interrelation Between the Adrenergic And The Imidazolinementioning
confidence: 99%